Cathodic Disbondment of Nano Ceramic Coating - Wan Mohd Nasir, Wan Mohamad Hafiz (IRC, 2018)
Corrosion prevention method for underground gas pipeline is commonly protected by external coating and cathodic protection. The consequence of excessive cathodic protection potential can cause the coating disbond with that compromise the integrity of pipeline and mechanical damage. The possibility of utilising robust nano ceramic coating for the underground coating and resist cathodic disbondment were not well studied. Therefore, the objectives of this project are to assess the performance of nano ceramic coating compare to conventional coating based on physical testing of pencil hardness testing and cathodic disbondment testing and to evaluate the degradation of the nano ceramic coating compare to the conventional coating based on cathodic disbondment testing comply to ASTM G8: Standard Test Methods for Cathodic Disbonding of Pipeline Coatings. The samples are tested with different applied potential of -800 mV, -1000 mV and -1500 mV in 3.5% of NaCl solution for 720 hours (30 days). After the experiment been done, several evaluations are made to validate the coatings performance such as corrosion observation, assessment degree of coating blistering, the dry film thickness after testing and the disbondment of the coating itself. By the end of the experiment, nano ceramic coating degrade more than conventional coating because the quality of colour pigment and resin that been use in nano ceramic is low quality compare to conventional coating. It is recommended to use carbon steel samples with the same thickness and coat the samples with same dry film thickness at the beginning of the experiment.